Design of optical-electronic sensor for ablation of spacecraft heat protection - Hornostaev, G.; Pasichny, V.; Lytvynenko, Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Results of designing and studying the characteristics of the fiber-optic sensor
for the ablation of the low-sublimating heat protection which intended for the use on the
being got down module of article “Mars-5” are represented. The originality of
development consists of guarantee for continuous measurement of the instantaneous
value of thickness of heat protective coating of the article during its descent. Achieving
this goal is ensured by the application of two light-guide sensors, one of which is made
from color glass-light filter.